Maqasid al-Sharia and the digital data ownership: From al-Shatibi to Jasser Auda - Thoriquttyas, Titis; Rohmawati, Nita (Journal of Islamic Law on Digital Economy and Business, 2026)
Purpose – Contemporary secular data protection issues are structurally inadequate to address digital data ownership. Despite consent-based and privacy-centered models, data subjects often lack meaningful control over economically exploitable data assets, while large platforms relate to asymmetrical informational access. This study responds to this failure by integrating classical and systems-based maqasid al-Sharīa to construct a principled Islamic framework for digital data ownership. Methodology – This study uses qualitative, doctrinal, and descriptive-analytical techniques based on library-based research. Al-Shatibi’s traditional maqāṣid framework and Jasser Auda's systems-based theory are examples of primary sources in recent academic works on Islamic legal theory. Thematic analysis and conceptual synthesis were used in the analysis, focusing on methodological evolution and continuity within maqasid al-Sharīa rather than comparison. Findings – This study finds that al-Shatibi’s maqasid paradigm, which emphasizes harm reduction, public welfare, and the preservation of important interests, offers crucial normative underpinnings for digital data ownership. However, it also highlights the structural shortcomings in dealing with the intricacy and systemic characteristics of digital data operations. By adding human dignity, systemic responsibility, and future-focused ethical reasoning, Jasser Auda's systems-based approach improves upon classical maqasid. Implications – By presenting maqasid al-Sharīa as a dynamic ethical system that can interact with digital governance and data ethics, the suggested integrated maqāṣid framework advances contemporary Islamic legal theory. Originality – Rather than merely comparing classical and modern maqasid theories, this study reconstructs digital data ownership as an urgent normative-economic problem and advances an integrated Islamic solution that is responsive to contemporary technological power structures.